Eksplorasi Pemahaman Siswa terhadap Konsep Akidah dalam Ilmu Kalam pada Pembelajaran PAI di SMP Negeri 3 Sugio: Exploring Students’ Understanding of Aqidah Concepts in Ilm al-Kalam: A Study in Islamic Education at SMP Negeri 3 Sugio - Nicky Estu Putu Muchtar; Nafisa Muchsin (Educan, 2026)
This research is based on understanding faith in students. The purpose of this study is to find out how to explore students' understanding of the concept of faith in the science of kalam taught through learning Islamic religious education and to find out the supporting and inhibiting factors in exploring students' understanding of the concept of faith in the science of kalam taught through Islamic religious education learning. This study uses a qualitative type of case study research, with data collection using observation, interview, and documentation techniques. As for the results of this study, the first is a way to explore students' understanding of the concept of faith in the science of kalam taught through Islamic religious education learning at SMP Negeri 3 Sugio carried out using the learning method of lectures, discussions, demonstrations, giving stories, associated with learning materials, giving questions and assignments to students, and reading and writing tests of the Qur'an. The second is the supporting factor in exploring students' understanding of the concept of faith in the Science of kalam taught through Islamic religious education learning, namely the selection of the right learning method, the high motivation of students to learn, an environment that reflects the values of faith in the science of kalam and the morning program of recitation. The factors that are inhibiting are the low motivation of students to learn, the low concern of parents, and the environment which does not reflect the values of faith in the science of kalam.